Unveiling toxigenic Fusarium species causing maize ear rot: insights into fumonisin production potential - Singh, Harinder; Kaur, Harleen; Hunjan, Mandeep Singh; Sharma, Smriti (Frontiers in Plant Science, 2025)
Fusarium species are widespread pathogens of maize (Zea mays L.), leading to various diseases throughout the plant’s lifecycle, including Fusarium ear rot (FER), a significant disease that impacts both yield and quality. FER begins at the silking stage when Fusarium conidia infect maize silks, particularly in tropical regions where F. verticillioides and F. proliferatum dominate. These pathogens not only lead to economic losses but also produce mycotoxins such as fumonisins, posing significant health risks to humans and animals. This study aimed to identify toxigenic Fusarium species associated with maize ear rot in North India and evaluate their fumonisin production potential under laboratory conditions. Out of the 48 Fusarium isolates collected, 40 amplified VERTF-1/2 primers, 41 amplified the FUM1 gene, while 36 amplified the FUM13 gene, indicating their potential to produce fumonisins. Sequencing analysis revealed that F. verticillioides was the predominant species associated with FER under North Indian conditions, with Fus 48 being identified as F. proliferatum. To assess their fumonisin production potential, Fus 15- the most virulent F. verticillioides isolate along with F. proliferatum isolate- Fus 48 were selected for further analysis. These isolates were artificially inoculated onto maize grains of PMH 1 and PMH 2 hybrids and fumonisin (FB1 and FB2) levels were quantified using liquid chromatography-mass spectrometry (LC-MS/MS). The results revealed that F. verticillioides (Fus 15) exhibited a higher fumonisin production capacity than F. proliferatum (Fus 48), with significantly greater fumonisin accumulation in PMH 2 hybrid. This increased fumonisin production in PMH 2 was positively correlated with FER severity under field conditions. Overall, this study provides critical insights into the prevalence and toxigenic potential of Fusarium species in North India, which could inform future management strategies to mitigate the impact of FER and its associated mycotoxins on maize production.